2010
DOI: 10.1557/jmr.2010.0299
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale strength distribution in amorphous versus crystalline metals

Abstract: Low-load nanoindentation can be used to assess not only the plastic yield point, but the distribution of yield points in a material. This paper reviews measurements of the socalled nanoscale strength distribution (NSD) on two classes of materials: crystals and metallic glasses. In each case, the yield point has a significant spread (10-50% of the mean normalized stress), but the origins of the distribution are shown to be very different in the two materials classes. In crystalline materials the NSD can arise f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 73 publications
4
42
2
Order By: Relevance
“…With nanoindentation testing, Schuh et al [57][58][59][60] found hardening of BMG, rather than softening, via cyclic loading in the elastic range. Sun et al [61] also presented a Bauschinger-type effect when BMGs were loaded under pure shear stress reversal in the elastic range.…”
Section: Correlation Of Fatigue Cracking Threshold With Fracture Tougmentioning
confidence: 99%
See 1 more Smart Citation
“…With nanoindentation testing, Schuh et al [57][58][59][60] found hardening of BMG, rather than softening, via cyclic loading in the elastic range. Sun et al [61] also presented a Bauschinger-type effect when BMGs were loaded under pure shear stress reversal in the elastic range.…”
Section: Correlation Of Fatigue Cracking Threshold With Fracture Tougmentioning
confidence: 99%
“…Secondly, the triaxial stress state ahead of the crack tip is completely different from that under the indenter [57][58][59][60] and torsional loading [61]: tensile mean stresses dominate ahead of the crack tip, while compressive mean stresses surround the indent. As indicated by Flores et al [63,64], the former stress state increases, while the latter decreases, the free volume in BMGs.…”
Section: Correlation Of Fatigue Cracking Threshold With Fracture Tougmentioning
confidence: 99%
“…Strongly and weakly bonded regions have been postulated to account for ,5 nm zones of accelerated crystallization 9 . The initial yield load (in nanoindentation) shows a dispersion of values associated with structural heterogeneity 10 . Mapping of heterogeneity by atomic-force microscopy, over areas much larger than in simulation, shows variations of energy dissipation 11 and of elastic modulus (,30%) 12 with correlation lengths of 2.5-20 nm.…”
mentioning
confidence: 99%
“…As mentioned earlier, the distribution of weak zones mimics the presence of intrinsic nanoscale density fluctuations in brittle metallic glasses (Packard et al, 2010;Wagner et al, 2011;Murali et al, 2011).…”
Section: Cavitation In Heterogeneous Plastic Solidsmentioning
confidence: 53%
“…They traced the origin of the above cavitation behavior in the brittle MG to the presence of strong atomic density fluctuations which gives rise to distributed weak zones. In this connection, it must be mentioned that Packard et al (2010) have reported from their low load nanoindentation experiments on MGs the presence of significant spread of 10-50% in nanoscale strength distribution, which has been attributed to fluctuation in their sampled structure. Also, Wagner et al (2011) measured the indentation modulus on the nanometer scale in Pd-based MGs using atomic force acoustic microscopy and found around 30% http://dx.doi.org/10.1016/j.ijsolstr.2014.09.005 0020-7683/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 98%